Transformasi Pembelajaran Pendidikan Agama Islam di Era Digital: Modalitas Belajar dan Tantangan Pendidikan di Abad 21 - Ghufron, David Maulana (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
This study aims to: 1.) Explain about how the transformation of PAI learning in the digital era, 2.) Describe the modalities of PAI learning in the development of digital technology and 3.) The qualitative method of literature study was used in this study. Books, articles, journals, and others, which are relevant to the topic of the research, were used as references in data collection. This study shows the importance of changing learning models that follow technological advances to improve the efficiency and effectiveness of education, applying the three learning modalities of visual, audio, and kinesthetic with PAI learning in technological developments, and the challenges of PAI learning in the 21st century in the form of poor education and resulting poor human resources. This study can be used as a reference in developing insights about PAI learning. Readers are expected to know the transformation of Islamic Education learning in the 21st century along with the challenges faced.